1999
DOI: 10.1007/bf02561525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyclonal immunoglobulins on neutrophil phagocytic capacity and reactive oxygen production in patients with gram-negative septicemia

Abstract: The effect of immunoglobulin (Ig) preparations on neutrophil phagocytic ability and oxidative burst in response to Escherichia coli stimulation was analyzed in 14 patients with gram-negative septicemia by an ex vivo whole blood assay using flow cytometry. In patients, neutrophils exhibited a decreased capacity to phagocytize E. coli and generate reactive oxygen products compared to healthy controls (median -68%, P < 0.01). The addition of both 7S-Ig and 19S-Ig enriched preparations in vitro resulted in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
3
9
0
1
Order By: Relevance
“…Our findings are in agreement with previous reports showing a high ROS generation in critically ill patients that developed sepsis (17). However, Wenisch et al (18) found a decreased ROS generation in patients with gram-negative sepsis, corroborating their previous results. Respiratory burst is one of the most important neutrophil defenses to control bacterial infection (6).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our findings are in agreement with previous reports showing a high ROS generation in critically ill patients that developed sepsis (17). However, Wenisch et al (18) found a decreased ROS generation in patients with gram-negative sepsis, corroborating their previous results. Respiratory burst is one of the most important neutrophil defenses to control bacterial infection (6).…”
Section: Discussionsupporting
confidence: 95%
“…This result is supported by previously reported findings in patients with sepsis (21) and is in agreement with data showing that primed neutrophils from healthy volunteers present an enhanced phagocytosis activity (10). On the other hand, studies using E. coli as stimulus showed a decreased phagocytosis in patients with gramnegative sepsis (18).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Lima et al (53) have reported that autophagy and phagocytosis are interdependent and complementary to each other. A decrease in phagocytosis by neutrophils was observed as a result of E. coli -induced sepsis in humans by Wenisch et al (54). In another study, Krasnodembskaya et al (55) have reported an increase in phagocytosis as a result of intervention with mesenchymal stem cells in mice with sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we investigated whether an increased resting burst in patients with liver cirrhosis is associated with an impaired respiratory burst capacity in response to bacteria. We hypothesized that, in the presence of subclinical endotoxaemia and clinically manifested infection, phagocytes are less responsive to Escherichia coli and their respiratory burst capacity becomes exhausted, as has been demonstrated previously for critically ill non-cirrhotic patients with systemic inflammatory response syndrome (SIRS) [29] and Gramnegative septicaemia [30]. To confirm our hypothesis and to determine the significance of elevated ROS production, the endotoxaemia marker LBP [31], the acute-phase reactant C-reactive protein (CRP) and immunoglobulin (Ig)G autoantibodies against oxidized low-density lipoproteins as a marker of lipid peroxidation in vivo [32,33] were correlated with respiratory burst activity in neutrophils and monocytes from patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 98%